Can International Law be Enforced Towards its Subjects Within the International Legal Order? - Muhammadin, Fajri Matahati (Jurnal Hukum IUS QUIA IUSTUM, 2016)
Can international law be enforced? This begs a question, thus problem, in the theory of law: whether there can be enforcement of law in absence of sovereign authority, as is the case of International law. International law has become its own legal order with its own unique way of operating. This writing is a normative research on the sources and reality of the actors of international law. It is found that international law is enforceable and that there are two ways that international law can be enforced, i.e. enforcement by “authorities” formed by treaty regimes, and by non-authorities (including enforcement individual states and by the international community). It is also found that these enforcement means have their weaknesses.